Model Pengembangan Wisata Berkelanjutan: Studi Kasus Desa Wisata Lerep Kabupaten Semarang - Nurjannah Rahayu Kistanti; Dyah Maya Nihayah; Syifa Sa’adah; Badar Fadlan Ibrahim; Dewi Karisma; Medi Elfani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this research is to analyze the sustainable tourism development model in Lerep Tourism Village, Semarang Regency. The data collection method was conducted by primary survey in the form of participatory Business Model Canvas (BMC) workshop to identify the economic potential of the village (tourism sector) and exploring through semi-structured interviews to several village stakeholders using purposive sampling. This data was analyzed using descriptive and SWOT analysis. The results showed that tourism development in Lerep Village requires improvement efforts in several aspects of BMC. By applying a framework such as the Business Model Canvas (BMC), Lerep Village can specifically identify different market segments and value propositions, thus enabling a coherent development approach. In order to implement the concept of community-based tourism (CBT) in various villages, a strong synergy between the government, the community, and the private sector is needed in formulating and realizing the vision of a sustainable tourism village.